2021
DOI: 10.12688/wellcomeopenres.16991.1
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the evidence of outdoor air pollution on asthma hospital visits in children and adolescents in South Asia – a call for data

Abstract: Background: Outdoor air pollution and childhood asthma are increasing problems in South Asian countries. However, little is known about the associations between levels of air pollution and severe childhood asthma requiring hospital treatment in these regions. Methods: We undertook a systematic review to assess the evidence between outdoor air pollution exposure and childhood and adolescent asthma hospitalization in South Asia. MEDLINE, Web of Science, Google Scholar, CINAHL, Embase, Scopus, ProQuest Central da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…40 While the prevalence of asthma in many developing countries of South Asia is increasing, very few studies determined the risk factors for this increase. 34 The prevalence of asthma increased with the increase of age among the respondents of this study. This study also found that the prevalence of asthma was quite high (6.0% or more) among those who were more than 60 years of age, ever smokers, underweight and those with comorbidities besides asthma or with family history of asthma.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…40 While the prevalence of asthma in many developing countries of South Asia is increasing, very few studies determined the risk factors for this increase. 34 The prevalence of asthma increased with the increase of age among the respondents of this study. This study also found that the prevalence of asthma was quite high (6.0% or more) among those who were more than 60 years of age, ever smokers, underweight and those with comorbidities besides asthma or with family history of asthma.…”
Section: Discussionmentioning
confidence: 54%
“…While the prevalence of asthma in many developing countries of South Asia is increasing, very few studies determined the risk factors for this increase 34. The prevalence of asthma increased with the increase of age among the respondents of this study.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Asthma in children is an important global health burden [ 5 ]. Several environmental, individual, and familial factors are associated with hospitalisation for asthma in children [ 6 , 7 , 8 , 9 , 10 , 11 ]. Understanding the triggers for hospitalization is important, as a high rate of admissions is a burden on the individual, the carer, and the hospital system.…”
Section: Introductionmentioning
confidence: 99%